Analisis Persepsi Mahasiswa Terhadap Perkuliahan Daring ditengah Pandemi Covid 19 - Irawan, Sapto; Saputra, Dwi Aji (JURNAL KONSELING GUSJIGANG, 2023)
The presence of the COVID-19 virus has changed various ways of life, including in the field of education from face-to-face to online. Efforts to provide lecture services to students are carried out using online learning platforms. Using Flexible Learning at SWCU Salatiga as a platform for online lectures, it is necessary to know the extent of students' perceptions of online lectures. This study aims to explore student perceptions of the implementation of online lectures in the midst of the COVID 19 pandemic. The instrument in this study used a questionnaire. This research uses survey method. The results of this study indicate that the perception of online lectures is quite positive and is in the fairly high category. This is evidenced by the percentage of 50% indicating quite high, 27% high and 23% quite low